Synchronic Analysis of the Progressive Aspect in Three Varieties of Asian Englishes - Salles-Bernal, Soluna (Miscelánea: A Journal of English and American Studies, 2015)
The purpose of this study is to analyse the frequency of use of the progressive aspect in three varieties of Asian Englishes, namely Hong Kong, India and Singapore, considering British English as a point of departure. The use of the progressive will be researched in comparable corpora (International Corpus of English) considering its distribution in the English verbal paradigm and subject person, both in the written and spoken components. Main results indicate that IndE has the highest frequency of the progressive, and Hong Kong English the lowest, when non-native varieties are compared. In all cases, the progressive is more frequent in the spoken than in the written section, and it preferably occurs in the present simple tense. English varieties present significant differences regarding the distribution of the progressive by tense and subject person. Several factors are discussed as possible reasons for such variation.